Prevalencia Y Razones De Consumo De Los Esteroides Anabólicos Por Parte De Usuarios Hombres De Gimnasios De La Ciudad De Armenia (2014)
The present research project presents the results obtained after the application of a statistical survey, which sought the prevalence and reasons for the consumption of Anabolic Androgenic Steroids in users men of gyms in the city of Armenia. Number of cycles, diseases, means acquisition of anabolic steroids, reasons for attending the gym, and intensity (days, hours), worked in the population evaluated variables were age, gender, consumption rate, type of drugs. The population evaluated standardized between ages of 18 and 45 years, which was applied a survey that would determine the reasons and the prevalence of the use of anabolic steroids. The information provided through tables in Excel that projected the conclusive results to know the reasons and the prevalence of anabolic steroids is tabulo. Please expand and direct an investigation to another kind of population that also uses this type of drug.